Degree Certificate Authentication using Cryptography, Digital Signature and QR Code Techniques (Journal of Hama University, 2019)
The field of information security plays an important role in the protection and security of information. One of the most important areas of information security is cryptography, which occupies today a prominent place among the sciences. Its practical applications have varied to many fields. The scope of applications of cryptography has expanded greatly in modern times after the development of communications and the Internet. And the need to ensure that prevention of eavesdropping and Spyware, electronic piracy and securing e-commerce. Electronic voting techniques and digital criticism are practical cryptographic applications. The most important of these technologies is the digital signature, which is used to sign most electronic documents from contracts, agreements and transactions with the possibility of encryption. Where it is used to verify the reliability of the owner of the information in addition to the authenticity of the information itself.This study propose a method to solve the problem of forging certificates using digital signature technology on the certificate based on the DSA algorithm one of the most important asymmetric encryption algorithms. The basic idea is to give the certificate site two related keys, called the public key, and the private key. Where the private key is used to sign the certificate and the public key is used by any person to verify the validity of the signature. In addition, the QR code was used to save the textual contents of the document, whatever its size, in a concise manner suitable for printing and reading. This proposed method will be a practical solution in securing official paper documents and protecting them from forgery, thereby increasing the confidence of local and international institutions in the official documents signed digitally.